Fabrication and characterization of dense BaCo0.7Fe0.2Nb0.1O3−δ tubular membrane by slip casting techniques. Issue 1 (January 2015) - Zhang, Yuwen; Zeng, Fanlin; Yu, Chenchen; Wu, Chengzhang; Ding, Weizhong; Lu, Xionggang
Abstract: The qualified green BaCo0.7 Fe0.2 Nb0.1 O3− δ (BCFNO) tubular membranes with length of 700 mm were successfully prepared using the most cost effective slip casting techniques. The optimum slurry composition was identified and some primary factors affecting microstructures, relative density and mechanical strength of membrane tubes were studied in details. Vertical sintering was developed to sinter the long membrane tubes. Dense and defect-free BCFNO membrane tubes with a length of around 560 mm were successfully achieved after the optimized controlled sintering process. A high oxygen permeation flux of 12 cm 3  cm −2  min −1 was achieved under the gradient of COG/air at 875 °C over 90 h. This simple and cost-effective fabrication technique can be used for mass production.